2004
DOI: 10.1097/01.sle.0000129382.85901.d8
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal, Cost-effective Laparoscopic Appendectomy Technique for Our Surgical Residents

Abstract: Since early 1999, we have implemented a standardized technique for laparoscopic appendectomy, which is simple, safe and easily learned and mastered by our residents. Besides superior ergonomics, it offers cosmetic advantages. It is inexpensive as only reusable instruments are used. It incorporates useful modifications, such as the use of suprapubic ports, inferior approach with repositioning of the videoscope from the umbilical port to the left suprapubic port, laparoscopic gauze swabs and instrument-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
(22 reference statements)
2
15
0
1
Order By: Relevance
“…We found that patient outcomes in resident-performed laparoscopic appendectomies in our study were comparable to those quoted in previous studies [8,20]. When we compared the two groups, we found significant reduction in operative duration and complication rates.…”
Section: Discussionsupporting
confidence: 90%
“…We found that patient outcomes in resident-performed laparoscopic appendectomies in our study were comparable to those quoted in previous studies [8,20]. When we compared the two groups, we found significant reduction in operative duration and complication rates.…”
Section: Discussionsupporting
confidence: 90%
“…As a routine, we thoroughly swab the peritoneal and pelvic cavity only after sucking out all exudates at the end of a laparoscopic appendectomy for severe appendicitis with localized soiling. In a recent audit of 713 laparoscopic appendectomies, our overall postoperative intraabdominal abscess rate stood at 0.7%, which compares favorably with figures from most reported laparoscopic appendectomy series (average of 15 series, 1.82%), while being comparable to that of open appendectomy (average of 15 series, 0.83%), despite the fact that 98.6% of the cases were done by surgical residents in an emergency setting [7].…”
Section: The Versatile Laparoscopic Spongesupporting
confidence: 74%
“…There is very little level I evidence comparing particular techniques, however some level II and III evidence suggests that developing a consistent method decreases costs and OR time and decreases complications [20,33]. This applies to laparoscopic appendectomy performed in a training program.…”
Section: Historical Contextmentioning
confidence: 95%